Realization of a half-metallic state on bilayer WSe2 using doping transition metals (Cr, Mn, Fe, Co, Ni) in its interlayer. (2nd February 2018) - Yang, Guang; Yang, Yanmin; Ma, Hongran; Mao, Xiujuan; Li, Congcong; Li, Jie; Zhang, Qiang; Zhang, Zhidong; Yin, Fuxing; Li, Jia
Abstract: The structural, electronic and magnetic properties of Cr, Mn, Fe, Co and Ni-doped bilayer WSe2 are predicted by using first principles calculations. The doped transition-metal (TM) atoms show a covalent-binding with the nearest Se atoms. The calculated electronic structures reveal that the TM Cr, Mn, Fe and Co-doped bilayer WSe2 exhibits a half-metallic character with a 100% spin polarization at the Fermi level, and the reason is ascribed to the strong hybridization peak between the transition metals and the parent W and Se atoms. The Ni-doped bilayer WSe2 is still a semiconductor with nonmagnetism. The Fe-doped system has a robust stability of half-metallicity because there are three connected states peak spanning the Fermi level. The doping of Cr, Mn, Fe and Co atoms leads to a prominent total magnetism (0.93–3.65 μ B moment per unit cell), and an induced ∼0.3 μ B moment in parent W atoms is found in addition to the main contribution of TM atomic magnetism (0.71–3.33 μ B moment per atom). The predicted Cr, Mn, Fe and Co-doped bilayer WSe2 should be the candidate materials for spintronic devices due to their magnetic and half-metallic nature.